Racial and Sexual Minority Scholar Positionality: Advancing Health Status and Life Opportunity Among Sexual Minority Men of Color. (June 2021) - Keene, Lance; Guilamo-Ramos, Vincent
Black and Latino sexual minority men (BLSMM) scholars are well positioned to draw on their unique perspectives and expertise to address the health status and life opportunities (HSLO) of BLSMM. Increasingly, research related to the positionality of scholars of color suggests that the scholar's stance in relation to the community being researched has important implications for the research. Despite growing recognition of the importance of scholar positionality, limited attention has been paid to the relationship between scholar-of-color positionality and improving HSLO trajectories of BLSMM. Furthermore, extant literature fails to specify the mechanisms by which scholar-of-color positionality can improve HSLO among BLSMM. This article seeks to fill this gap in research by arguing that an inadequate consideration of scholar positionality in health and life opportunity research has important implications for the HSLO of BLSMM. A multilevel, mediational model addressing factors at the micro-level (i.e., intrapersonal resources)—BLSMM scholars' personal commitments to BLSMM communities, cultural knowledge and expertise, and shared life experiences; meso-level (i.e., scholar and affected community interactions)—historical membership, mutual interdependency and trust, and community and organizational gatekeeping; and macro-level (i.e., national policies and priorities regarding BLSMM)—national priorities regarding the health and social welfare of BLSMM, allocation of BLSMM research and program funding, societal sentiment, and national investment in the workforce development of BLSMM scholars and clinicians are detailed. In conclusion, we identify recommendations and strategies for advancing scientific, programmatic, and policy efforts, aimed at improving HSLO among communities of BLSMM.